2003
DOI: 10.1038/sj.leu.2403087
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific chimaerism after stem cell transplantation in children following reduced intensity conditioning: potential predictive value of NK cell chimaerism for late graft rejection

Abstract: Chimaerism of FACS-sorted leucocyte subsets (CD14 þ , CD15 þ , CD3À/56 þ , CD3 þ /4 þ , CD3 þ /8 þ , CD19 þ ) was monitored prospectively between days þ 14 and þ 100 in 39 children undergoing allogeneic stem cell transplantation with reduced intensity-conditioning regimens. Cell subsets exceeding 1% of nucleated cells were subject to cell sorting. Chimaerism was analysed by dual-colour FISH and/or by short tandem repeat-polymerase chain reaction. The chimaerism pattern on day þ 28 was evaluated with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…1,4,23 When rare cell subsets are isolated for subsequent chimerism analysis, the availability of sufficient amounts of DNA may become a limiting factor with regard to the achievable sensitivity and reproducibility of results. The experience among members of the EUC consortium indicated that the cell number available for analysis in these instances can be as low as a few hundred to a few thousand cells.…”
Section: Resultsmentioning
confidence: 99%
“…1,4,23 When rare cell subsets are isolated for subsequent chimerism analysis, the availability of sufficient amounts of DNA may become a limiting factor with regard to the achievable sensitivity and reproducibility of results. The experience among members of the EUC consortium indicated that the cell number available for analysis in these instances can be as low as a few hundred to a few thousand cells.…”
Section: Resultsmentioning
confidence: 99%
“…4,11,15 Andreani et al 13 showed an 84% rejection rate in patients with thalassemia who had 425% autologous cells in WB at 2 months post transplant, and Baron et al 1,2 and Matthes-Martin et al 5 showed that low donor CD3 þ and natural killer cell chimerism at days 14 and 28 post transplant correlated with graft rejection. Long-term follow-up of patients with thalassemia showed that once tolerance to donor cells has been established, graft rejection does not occur even at low levels (o10%) of donor WB engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 24 children (median age 7.6 years, range (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)) undergoing first unmodified allogeneic HSCT for a non-malignant disorder at University of California, San Francisco, (UCSF) Children's Hospital, Pediatric Blood and Marrow Transplant Unit (PBMTU) between January 2001 and March 2007. Only patients who received fludarabine-or cyclophosphamide-based conditioning regimen and had chimerism testing done by the STR technique were included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations